The Influence of Social Factors, Trust, Website Quality, and Perceived Risk on Repurchase Intention in E-Commerce - Axellino Tegar Hieronanda; Albert Kriestian Novi Adhi Nugraha (University of Merdeka Malang, 2021)
In recent years, internet shopping has become a culture to fulfill their needs, goods, and services. Many users of e-commerce services can be a chance to develop new business models, although the users may experience a certain amount of risk associated with their purchase. The purpose of this study is to examine (from a consumer perspective) the main aspects that affecting consumer's repurchase intentions through an e-commerce website. Specifically, the current study investigated the impact of social factors, trust, website quality, and perceived risk on repurchase intentions at Shopee e-commerce by using structural equation model analysis. The population is individual Shopee users in Indonesia. A sample consists of 238 respondents was obtained using the purposive sampling technique. The results indicate that social factors, trust, and website quality do not affect repurchase intentions in e-commerce. In contrast, risk affects repurchase intentions in e-commerce.